Photocatalytic Oxidation of Nitrogenous Fertilizers Using Cyclodextrin and Reduced Graphene Oxide Modified Metal-TiO2 Nanocomposites - Soni, Palak (TIET, 2025)
Chapter-1 This comprehensive introduction provides a solid foundation for understanding the role of nitroge- nous fertilizers, the challenges of nitrogen loss, and the potential of advanced nanocomposites in im- proving nitrogen utilization in agriculture is systematically explained in this chapter. However, sig- nificant nitrogen loss through volatilization, leaching, and emissions leads to environmental concerns and reduced crop efficiency. The research gap emphasizes the need for advanced nanocomposites like M-TiO2, reduced graphene oxide (RGO), and cyclodextrin (CD) to enhance nitrate production and minimize nitrogen loss. The proposed approach suggests that combining these materials could lead to more efficient photocatalytic oxidation of urea, improving nitrate conversion and reducing nitrogen-related environmental issues. Chapter-2 Nowadays, fertilizers are used to boost crop production. Nitrogenous fertilizers are assimilated as nitrate. Unfortunately, 60-70% of nitrogen is lost due to different leaching processes. Photocatalytic urea oxidation is now emerging as a new methodology. Nitrate conversion is favorable under alka- line ph. However, it can subsequently cause deprotonation of ammonium ions to result ammonia leaching. In this report, efficiencies of bare and RGO loaded TiO2 were examined. In the presence of NaF, the nanocomposite possesses a 9.8(1) % nitrate yield, significantly greater than the other analo- gous reactions. Such observation will be helpful in developing new methodologies to afford sustain- able agriculture. Chapter-3 Photocatalytic oxidation of urea is an essential area of study for converting urea to nitrate. As crops absorb nitrogen in the form of NO3− but due to incomplete oxidation, a substantial fraction of it es- capes into the atmosphere as N2. Hence, an effective photocatalyst is urgently needed to improve ni- trate conversion. This study focuses on the influence of β-cyclodextrin and Ag deposition on TiO2 towards the photocatalytic oxidation of urea. β-cyclodextrin (15-25 wt.%) and Ag (1-3 wt.%) loaded binary and ternary nanocomposites have been prepared using hydrothermal and photo deposition iv methods, respectively. The binary and ternary hybrids were characterized using FESEM, EDX, HR- TEM, XRD, XPS, DRS, PL, DLS, and FT-IR analysis. Photocatalytic urea degradation activity was evaluated under solar irradiation. The β-CD25/TiO2@Ag1 ternary nanocomposites show 78% degra- dation efficiency with 17.8% nitrate yield after 180 minutes reaction time which is the highest. This observation can be ascribed to the higher affinity of β-CD towards N2 due to the hydrophobic effect and the surface plasmon effect of Ag, which amplifies its visible light response. Such observations will attract much interest from a large section of material and agricultural chemists to design new catalysts for photochemical urea oxidation to afford sustainable agriculture. Chapter-4 Urea oxidation is important to increase agricultural growth, which can meet the food requirements across the world. It is pivotal for converting nitrogen to nitrate that is usable by crops, thus prevent- ing nitrogen loss to the atmosphere. This study focuses on improving the photodegradation efficiency of TiO2 by incorporating β-CD (beta-cyclodextrin), RGO (reduced graphene oxide), and Ag to en- hance nitrate conversion. FT-IR, DRS, PL, EDX, XRD, XPS, HR-TEM DLS, and FESEM were conducted to characterize these materials. Among all the catalysts, the quaternary composite, β- CD/ TiO2/Ag/RGO, exhibited superior performance, achieving an 86.2% degradation efficiency with a 27.8% nitrate yield under sunlight irradiation within 150 minutes of reaction time. Several factors contribute to the enhanced photoactivity of β-CD/TiO2/Ag/RGO, including the high surface area and absorptive power of β-CD, the high electron mobility of RGO, and the LSPR effect of Ag, extending the catalyst's response to visible light. An intriguing aspect of this study is the encapsulation of gase- ous nitrogen into the hydrophobic interior cavity of β-CD, contributing to the enhancement of urea oxidation. These findings can be very substantial for both agriculturists and chemists, providing val- uable insights into designing novel photocatalysts for improved urea oxidation, thereby enhancing agricultural,productivity.
Keywords: Photocatalysis; Nitrate production; Urea oxidation; Nitrogen utilization; β-cyclodextrin; Sustainable agriculture